Motive behind Earnings Management Practices: Case in Public Property and Real Estate Companies in Indonesia - Kustono, Alwan Sri (UNIVERSITAS NEGERI SURABAYA, 2020)
This study examines the antecedents and consequence variables of earnings management. This study is expected to explain the motive of earnings management practices by public property and real estate companies in Indonesia: opportunistic or efficient. The theory which is the basis for developing the hypotheses ise agency, positive accounting, and signaling theories simultaneously. This study is explanatory research which aims to explain the causal relationship between variables through hypothesis testing. Data of this research are financial statements of public companies in the property and real estate sector in Indonesia (2014-2018) with some criteria. There are 60 firm-years data used in the analysis. Hypothesis testing uses multiple linear regression two-stage. The first stage analysis is used to examine the effect of the antecedent earnings management variable. Regression second stage test the consequences of earnings management practices. The results show debt and independent commissioners affect earnings management. Management performs more dominant earnings management because of opportunistic interests than to maintain market value and the interests of its shareholders. The implication of this research is to provide a comprehensive discourse on the motives for earnings management behavior in Indonesia.